1984
DOI: 10.1149/1.2116049
|View full text |Cite
|
Sign up to set email alerts
|

Long Cycle‐Life Secondary Lithium Cells Utilizing Tetrahydrofuran

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 3 publications
1
50
0
Order By: Relevance
“…Much effort has been exerted to improve the surface uniformity of SEI layers and to form electrochemically stable SEI layers. Several approaches have been pursued to improve the rechargeability and reliability of the metallic lithium electrode: i) the use of liquid or polymer electrolytes that are less reactive toward lithium electrodes; [71][72][73][74][75][76][77] ii) the protection of lithium electrodes by adding surface active agents such as hydrocarbons and quarternary ammonium salts; [ 78 , 79 ] iii) the formation of Li 2 CO 3 , LiF, LiOH, or polysulfi de by using CO 2 , [ 74 , 80-86 ] HF, [87][88][89][90] water trace, [ 74 , 81 , 91 ] and S x 2 − ; [ 80 , 92 ] iv) the formation of a stable metal alloy (LiI) by incorporating SnI 2 or AlI 3 ; [ 93 ] v) the use of surfactants such as non-ionic polyether compounds; [ 94 ] vi) uniform lithium deposition by means of pressure and temperature; [ 70 , 95 , 96 ] vii) the removal of impurities from the interface of lithium metal and electrolyte with an inorganic fi ller such as silica, alumina, zeolite, or titanate, [97][98][99][100][101][102] viii) the suppression of lithium dendrites by the formation of an ultra-thin polymer electrolyte layer based on plasma polymerization or UV irradiation polymerization. [103][104][105][106][107] The formation of a stable SEI layer on the lithium metal surface can be promoted by adding agents such as CO 2 , HF, or S x 2 − , and, thus, the dendritic lithium formation can be greatly suppressed.…”
Section: Surface Modifi Cationmentioning
confidence: 99%
“…Much effort has been exerted to improve the surface uniformity of SEI layers and to form electrochemically stable SEI layers. Several approaches have been pursued to improve the rechargeability and reliability of the metallic lithium electrode: i) the use of liquid or polymer electrolytes that are less reactive toward lithium electrodes; [71][72][73][74][75][76][77] ii) the protection of lithium electrodes by adding surface active agents such as hydrocarbons and quarternary ammonium salts; [ 78 , 79 ] iii) the formation of Li 2 CO 3 , LiF, LiOH, or polysulfi de by using CO 2 , [ 74 , 80-86 ] HF, [87][88][89][90] water trace, [ 74 , 81 , 91 ] and S x 2 − ; [ 80 , 92 ] iv) the formation of a stable metal alloy (LiI) by incorporating SnI 2 or AlI 3 ; [ 93 ] v) the use of surfactants such as non-ionic polyether compounds; [ 94 ] vi) uniform lithium deposition by means of pressure and temperature; [ 70 , 95 , 96 ] vii) the removal of impurities from the interface of lithium metal and electrolyte with an inorganic fi ller such as silica, alumina, zeolite, or titanate, [97][98][99][100][101][102] viii) the suppression of lithium dendrites by the formation of an ultra-thin polymer electrolyte layer based on plasma polymerization or UV irradiation polymerization. [103][104][105][106][107] The formation of a stable SEI layer on the lithium metal surface can be promoted by adding agents such as CO 2 , HF, or S x 2 − , and, thus, the dendritic lithium formation can be greatly suppressed.…”
Section: Surface Modifi Cationmentioning
confidence: 99%
“…The polarization, TI, vs. current density, j, for pure sodium and a composite electrode, Na, PPP(19 w/o)/Na2.2sPb(77 w/o)/EPDM(4 w/o). pressed in accordance with the linearized Butler-Volmer equation (14) j = joF ~/RT [1] where jo is the exchange current density, and R, T, and F are the gas constant, temperature, and the Faraday constant, respectively. Using Eq.…”
Section: Behavior Of the Composite Electrode In A Balanced Cell-mentioning
confidence: 99%
“…The sharp Li filaments can pierce through the separator with increasing cycle time, thus provoking internal short-circuiting (12). Most previous academic research to settle this bottleneck focuses on solid electrolyte interphase (SEI) stabilization/modification by introducing various additives (13)(14)(15)(16)(17). These electrolyte additives interact with Li quickly and create a protective layer on the Li metal surface, which helps reinforce the SEI (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Most previous academic research to settle this bottleneck focuses on solid electrolyte interphase (SEI) stabilization/modification by introducing various additives (13)(14)(15)(16)(17). These electrolyte additives interact with Li quickly and create a protective layer on the Li metal surface, which helps reinforce the SEI (13)(14)(15)(16)(17). Furthermore, recent study in our group has also shown the employment of interconnected hollow carbon spheres (18) and hexagonal boron nitride (19) as mechanically and chemically stable artificial SEI which effectively block Li dendrite growth.…”
mentioning
confidence: 99%